PENGARUH PERMAINAN KARTU HURUF BERGAMBAR TERHADAP MOTIVASI BELAJAR ANAK DALAM MENGENAL HURUF PADA ANAK USIA 4-5 TAHUN DI PAUD AS-SHIFA CITRA PEKANBARU - Susila '; Wusono Indarto; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract:This research aim to know the influence of pictured letters card game to motivation learn in recognizing letters in children aged 4-5 years at paud as-shifa citra pekanbaru. Population of this reseacrh was paud as-shifa citrapekanbaru child’s, sample of researchare 20 childs. Method of research was experiment which this research tries to look for this research aim to know the influence of pictured letters card game to motivation learn in recognizing letters in children aged 4-5 years at paud as-shifa citra pekanbaru. Instrumental of this research used observation sheet. Data anlisa tech used utilizes scale test-driving and statistical methods analysis with SPSS For's program ver's Windows 20. The result of this research that acquired available the influence of pictured letters card game to motivation learn in recognizing letters in children aged 4-5 years at paud as-shifa citra pekanbaru. Obtained value t tabel with df 19 in taraf signifikansi 5% (2-tailed) of 2,093. This known t count (17,472)>t table (2,093) or signifikansi (0,000)<0,05. Influence card game pictured letters to motivation learn children recognize letters in the age of 4-5 years in early childhood As- Shifa Pekanbaru that is equal to 70,588%.Key Words : Motivation Learn, Pictured Letters Card Game